PROJECTION OF THE 7Li{αt} WAVE FUNCTION ON THE 5Не{αn}+d CLUSTER CHANNEL. II RESULTS OF CALCULATIONS - Afanasyeva, N.V. (Recent Contributions to Physics, 2017)
Within the at-model for 7Li nucleus spectroscopic Sd-factors of deuterons separation have been calculated by using different 5Hean wave function models. A comparison with available theoretic calculations performed within the multiparticle shell model is given.